2016
DOI: 10.1155/2016/3797615
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Predictors for Lymph Node Metastasis in Patients with Superficial Esophageal Carcinoma

Abstract: In order to predict related risk factors for lymph node metastasis (LNM) in patients with superficial esophageal carcinoma (SEC) and provide reference for endoscopic minimally invasive treatment, we included a total of 93 patients with superficial esophageal carcinoma who have underwent esophagectomy and lymph node dissection from 2010 to 2015. The depth of invasion was remeasured and classified into 6 groups according to their wall penetration. The prediction model was founded based on the independent risk fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 25 publications
2
16
1
Order By: Relevance
“…In the current study, we assessed a retrospective collection of data on patients with ESCC in order to determine the prognostic value of LVI. The positive rate of LVI in this cohort was 32.2%, which was comparable with the rate reported in the literature (14)(15)(16)(17)(18) 128 patients to determine the prognostic significance of various clinical and histopathological factors for ESCC (19). These researchers reported that the presence of LVI significantly decreased the 5-year survival rate.…”
Section: Discussionsupporting
confidence: 88%
“…In the current study, we assessed a retrospective collection of data on patients with ESCC in order to determine the prognostic value of LVI. The positive rate of LVI in this cohort was 32.2%, which was comparable with the rate reported in the literature (14)(15)(16)(17)(18) 128 patients to determine the prognostic significance of various clinical and histopathological factors for ESCC (19). These researchers reported that the presence of LVI significantly decreased the 5-year survival rate.…”
Section: Discussionsupporting
confidence: 88%
“…Overall, lymph node status plays an important role in surgical strategy selection and prognosis[ 34 ]. The LNM rate of T1 ESCC has been reported to be 12.9%-45.0%, with a large deviation[ 18 , 28 , 35 ]. The results of this meta-analysis showed an LNM rate of 24.2%, and risk factors associated with LNM were tumor size, tumor location, T1 substage, tumor differentiation, LVI and macroscopic type.…”
Section: Discussionmentioning
confidence: 99%
“…T1 substage, tumor differentiation and tumor size have been indicated as predictors of LNM in several studies, and our study verified these results. Previous studies reported LNM rates in MM1, MM2, MM3, SM1, SM2 and SM3 of 0%, 1.5%-3.7%, 5.3%-30.8%, 8.7%-42.1%, 12.7%-40.7% and 28.4%-66.7%, respectively[ 14 , 16 - 18 , 21 - 23 , 35 ]. Submucosal tumors have a high risk of LNM, and there is no safe area for ER of T1b tumors[ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, with tumor diameter exceeding 3 cm, infiltration into submucosa and the lymph node involvement rate was high. Patients with lymphovascular invasion had significantly higher Lymph node metastasis than in patients without it (32.1% vs. 4.6%) (14).…”
Section: Editorial Ct2n0 Esophageal Adenocarcinoma: Predictors Of Lymmentioning
confidence: 86%
“…A research group from China, in their retrospective analysis of 93 cases of superficial esophageal carcinoma, reported the depth of invasion and degree of differentiation to significantly correlate with lymph nodal involvement (14). They emphasized the need for close follow up following endoscopic resection in m3 and sm1 diseases and considered surgical resection to be the treatment of choice for sm2 disease and above, which restated the stand that adequate lymphadenectomy is needed for complete clearance of the occult disease.…”
Section: Editorial Ct2n0 Esophageal Adenocarcinoma: Predictors Of Lymmentioning
confidence: 99%